Quantification of micro-scale variability in fibre bundles - Gommer, F.; Endruweit, A.; Long, A.C. (Elsevier, 2016)
Local variations in the random filament arrangement in carbon fibre bundles were determined by optical microscopy and automated image analysis. Successive steps of abrading, polishing and acquiring micro¬graphs of the sample surface made it feasible to analyse the micro-structure over a series of cross-sections along the fibre bundle path. Random and systematic changes in local filament arrangements were determined. Systematic changes were related to the interaction of a fibre bundle with an intersect¬ing binder thread leading to a local increase of the fibre volume fraction at the interface. Random clus¬tering of filaments in areas of high or low fibre volume fractions within the fibre bundles were found to be unaffected by the relative position of the bundle.